Comparisons of Different Dosages of Gonadotropin-Releasing Hormone (GnRH) Antagonist, Short-acting Form and Single, Half-dose, Long-acting Form of GnRH Agonist During Controlled Ovarian Hyperstimulation and in vitro Fertilization - Yao-Yuan Hsieh; Chi-Chen Chang; Horng-Der Tsai (Elsevier, 2008)
Summary: Objective: Both gonadotropin-releasing hormone (GnRH) analogs and antagonists have been used for pituitary desensitization during controlled ovarian hyperStimulation (COH). We aimed to determine the minimum effective daily dose of GnRH antagonist in women undergoing COH. We also compared the efficiency of a GnRH antagonist and a GnRH agonist. Materials and Methods: Women undergoing in vitro fertilization/intracytoplasmic sperm injection and embryo transfer were divided into five groups: (1) cetrorelix 0.25mg(n = 86); (2) cetrorelix 0.2mg(n = 28); (3) cetrorelix 0.15 mg (n = 30); (4) leuprolide acetate (LA) 0.5 mg/day (n = 58); (5) single half-dose LA depot 1.88mg (n = 49). Cetrorelix was administered daily from menstrual day 8 until the day of human chorionic gonadotropin administration. LA or LA depot was started on day 21 of the previous menstrual cycle. Results: We observed lower gonadotropin (Gn) dosages, estradiol (E2) levels and reduced risk of ovarian hyper-stimulation syndrome (OHSS) in the GnRH antagonist groups. A higher risk of luteinizing hormone (LH) surge was noted in cetrorelix0.2 and 0.15 mggroups. Gn dosages (IU)/E2 levels (pg/mL) in each group were: (1) 1,949.4/ 1,191.1; (2) 1,869.6/1,010.8; (3) 1,856.7/1,023.6; (4) 2,184.5/1,323.6; and (5) 2,103.5/1,313.5, respectively. LH/OHSS risks were: (1) 3.5%/5.8%; (2) 7.1%/3.6%; (3) 13.3%/3.3%; (4) 3.4%/8.6%; and (5) 2%/8.2%, respectively. Number of oocytes/embryos/grade I, II embryos were: (1) 9.4/7.9/5.8; (2) 7.5/4.2/3.6; (3) 6.3/4.1/3.1; (4) 12.3/ 8.9/6.6; and (5) 11.8/8.4/6.1, respectively. There was no significant difference in terms of clinical outcomes between groups 1, 4 and 5, except for higher abortion rates (AR) in group 1. Pregnancy rate (PR)/implantation rate (IR) ratios in groups 1, 4, and 5 were statistically higher than those in groups 2 and 3. Chemical PR/IR/AR were: (1) 30.2%/ 5.9%/7%; (2) 21.4%/5.1%/7.1%; (3) 16.7%/4.1%/10%; (4) 32.8%/5.5%/8.6%; and (5) 30.6%/5.7%/8.2%, respectively. Conclusion: The lowest effective dosage of cetrorelix for pituitary desensitization during COH luteolysis is 0.25 mg, resulting in a comparable PR but a higher AR when compared with GnRH agonist. Key Words: cetrorelix, GnRH agonist, GnRH antagonist, leuprolide acetate, pituitary suppression